Providing supplementary, artificial milk for large litters during lactation: effects on performance and health of sows and piglets: a case study. Issue 1 (December 2015) - Pustal, J.; Traulsen, I.; Preißler, R.; Müller, K.; Beilage, T.; Börries, U.; Kemper, N.
Abstract Background One possible way to support raising large litter sizes in pigs is to offer supplementary, artificial milkad libitum in the farrowing pen in addition to the sow's milk. In order to evaluate the potential use of this method and its effects on performance and health, supplemented (n  = 60) and control sows (n  = 60) with their litters were tested over 15 batches in one herd during one year. In the supplemented group (SG), piglets had access to supplementary milk in addition to sow's milk from their 2nd day of life until weaning (day 27). The litters of SG sows were adjusted to contain as many piglets as the sow had functional teats, whereas in the control group (CG), piglets were set to the number of functional teats minus one, due to animal welfare reasons. Case presentation With supplementary milk provision, the weaning of large litters was achieved without any negative impacts on performance and health. On average, 13.5 and 12.4 piglets were weaned in SG and CG, respectively (P  < 0.05). While average weaning weights (SG: 7.8 kgv . CG: 7.8 kg;P  > 0.05) and average daily weight gain of the piglets (SG: 0.25 kgv . CG: 0.25 kg;P  > 0.05) did not differ, total litter weight was consequently higher in SG than in CG (104.9 kgv . 96.7 kg;P  < 0.001). The average milk replacer intakes were 1.1 kg milk powder per day and batch, and varied significantly between the "warm" and "cold" seasons (1.5v . 0.9 kg milk powder per batch and day;P  < 0.001). No significant differences in the mortality rate or the occurrence of diarrhoea were detected in the piglets of both SG and CG (P  > 0.05). With regard to documented medical treatments, facial lesions were treated less frequently in piglets of SG (46v . 32 treatments;P  < 0.05). There was no effect of supplementary milk on the loss of body weight, backfat thickness and body condition score of the sows (P  > 0.05). Conclusions To summarise, in the presented case offeringad libitum supplementary, artificial milk supported the sow in raising large litters by compensating possible negative impacts of high piglet numbers on the weight gain of piglets and the body condition of the sows.